Evaluating Correlations between a Seaport and Its Dry Ports: Case Study of Xiamen Port in China - Jihong Chen; Yijie Fei; Fangwei Zhang; Chutao Jing (Discrete Dynamics in Nature and Society)
As bridges connecting seaports and their hinterland, dry ports serve to expand the hinterland and increase cargo sources of seaports, rendering efficient international logistics circulation in hinterland areas possible. The roles of dry ports have attracted increasing attention from various ocean shipping countries. Seaports and dry ports possess complementary functions and increasingly close interactions. The paper builds an assessment indicator system on correlations between seaports and dry ports and a two-stage grey relational analysis (GRA) method through collating dry port-related literature to facilitate quantitative studies on the correlations between seaports and dry ports, namely, using two quantitative indicators of Deng’s correlation and absolute correlation to assess and determine the correlations in the development of seaports and dry ports. The paper then carries out case studies on Xiamen Port and its six dry ports to verify the effectiveness of the method and model in the paper. The study results show that Xiamen Port has very high region-varying correlations with its hinterland dry ports. Dry port development not only depends on their shipment volume indicators, but also significantly correlated with their economic indicators, and the hinterland economic indicators become key factors driving the fast development of a seaport. The analyzing method in the paper is conducive for government departments and relevant stakeholders to formulate superior policies and provide theoretical bases for the development of correlations between seaports and their dry ports.